Frequency of rare, serious donor reactions: International perspective. Issue 6 (5th March 2021) - Young, Pampee; Crowder, Lauren; Steele, Whitney; Irving, David; Pink, Joanne; Kutner, Jose Mauro; Yokoyama, Ana Paula Hitomi; Van Buren, Nancy; O'Sullivan, Nicholas William; Sayers, Merlyn; Alcantara, Ramir Moreno; van den Hurk, Katja; et al.
Abstract: Background: Severe blood donor adverse events are rare, but due to their rarity studying them can be difficult. To get an accurate estimate of their frequency and rate in the donor population it may be necessary to combine donation data across countries. Study Design and Methods: International blood collection organizations (BCOs) provided data on rare/severe donor reactions as well as denominator information for their donor populations from 2015 to 2017. Donor reactions were classified using standardized definitions. Results: BCOs from six countries provided reaction data for more than 22 million donations. A total of 480 rare reactions were reported of which 76.7% were imputed as definite and 11% probable. Rates of rare reactions were higher in females and first‐time donors. Systemic rare reactions were the most common reaction type, accounting for over three quarters of reactions reported. Of systemic reactions, vasovagal reactions with loss of consciousness and injury or off‐site (n = 350) made up the majority and occurred 1.53 per 100, 000 donations. For the 22.3% that were localized reactions, the majority of these were cellulitis (n = 71, 0.31 per 100, 000 donations) followed by deep venous thrombosis (n = 21, 0.09 per 100, 000 donations). Conclusion: Pulling together data from multiple BCOs across countries allows for a better understanding of rare reactions, such as vasovagal reaction with injury or cellulitis, and for generating a reliable incidence rate for air embolism or compartment syndrome. However, gaps remain due to missing elements such as unknown donor status or location of reaction.